2019
DOI: 10.1111/scd.12435
|View full text |Cite
|
Sign up to set email alerts
|

Chronology and sequence of deciduous teeth eruption in children with microcephaly associated to the Zika virus

Abstract: IntroductionDeciduous teeth eruption is connected to children's growth and development. In Brazil, with the increase in the occurrence of children born with microcephaly associated to exposure to Zika virus, studies about orofacial alterations were necessary.ObjectiveDescribe the chronology and sequence of deciduous teeth in children with microcephaly due to the fetal exposure to Zika virus.MethodologyA cross‐sectional study involving 74 children of a neuropediatric reference unit in Salvador, Bahia, in 2017 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 18 publications
3
20
0
1
Order By: Relevance
“…However, studies focusing on this issue are still scarce in the literature. [4][5][6][7][8] As a result, the possibilities of interation with the literature are limited, making it often necessary to discuss the results from data observed in child. 23 Thus, unlike studies that analyzed a similar age range in the general population, [24][25][26][27] the occurrence of dental caries was not observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies focusing on this issue are still scarce in the literature. [4][5][6][7][8] As a result, the possibilities of interation with the literature are limited, making it often necessary to discuss the results from data observed in child. 23 Thus, unlike studies that analyzed a similar age range in the general population, [24][25][26][27] the occurrence of dental caries was not observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…2 Some clinical findings in children with microcephaly associated with ZIKV have already been published, such as brain changes, neurological abnormalities, 3 bone and craniofacial deformities. [4][5][6][7][8] Changes have also been reported in children with microcephaly caused by other causes, for example, impaired vision and hearing, delayed cognitive, motor and speech development 8,9 and epilepsy. 10 However, there are few studies describing the types and severity of oral changes in children with microcephaly associated with ZIKV.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Besides sex, other factors can alter the eruption chronology, either delaying or accelerating the process, such as birth weight (VERMA et al, 2017), eating habits (HOLMAN & YAMAGUCHI, 2005;VERMA et al, 2017), nutrition (BASTOS et al, 2007HOLMAN & YAMAGUCHI, 2005), socioeconomic status (BASTOS et al, 2007;VERMA et al, 2017), body mass index (VERMA et al, 2017), heredity (HATTON, 1955), systemic and local diseases D'AGOSTINO et al, 2020;LIMA et al, 2019), and regionality (HOLMAN & YAMAGUCHI, 2005;VERMA et al, 2017). Thus, it is observed that the variation in tooth eruption is multifactorial (VERMA et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Microcephaly is diagnosed after birth when the head circumference measures less than 32 cm -value considered ideal. 1,3 Patients with microcephaly may have multiple associated oral conditions, 5,6 including eruption cyst (EC), defined as a liquid cavity originating from dental epithelial tissues. 7 EC is a benign pathology, usually asymptomatic, that happens in a retained, impacted, non-erupted tooth or a tooth with late eruption, adjacent to the dental crown at the cementoenamel junction.…”
Section: Introductionmentioning
confidence: 99%